Increased physical activity post-exacerbation is associated with decreased systemic inflammation in cystic fibrosis – An observational study. (1st December 2020) - Burton, Kate; Morris, Norman R.; Reid, David; Smith, Daniel; Kuys, Suzanne
ABSTRACT: Background and Objective : We assessed whether measured physical activity in adults with cystic fibrosis (CF) following in-hospital treatment for an acute exacerbation was impacted by levels of systemic and airway inflammation, and whether physical activity post-discharge predicted for time to next pulmonary exacerbation. Methods : Adults with CF were included following hospitalization for a pulmonary exacerbation, and were followed for 12 months. Inflammatory markers and physical activity were measured immediately post-discharge via sputum and plasma concentrations of interleukin-6, interleukin-8, and tumor necrosis factor- α . Physical activity was monitored for 7 days via a Sensewear Armband. Statistical analyses included Shapiro-Wilk's test and Q–Q plots to determine normal distribution, t-tests, Pearson's correlational analyses, and one-way MANOVAs. Results : Thirty-one adults with CF (13 females, 28.8 ± 8.8 years, forced expiratory volume in 1 s (FEV1 ) 59.4 ± 23.0% predicted) were prospectively recruited. Physical activity negatively correlated with plasma inflammation ( r = −0.48, p < 0.01), and positively with FEV1 ( r = 0.45, p < 0.05) and body mass index (r = 0.39, p < 0.05). There was no significant relationship between time to re-exacerbation and any inflammatory markers or measurement of physical activity (all p > 0.05). Conclusion : Increased physical activity following exacerbation in CF is associated with lower levels of systemic inflammation. Time to re-exacerbation is not related to post-discharge inflammation or physical activity levels.